Assessment of Soil Functions: An Example of Meeting Competing National and International Obligations by Harnessing Regional Differences - Valujeva, Kristine; Nipers, Aleksejs; Lupikis, Ainars; Schulte, Rogier P. O. (Frontiers in Environmental Science, 2020)
The increased demand for bio based products worldwide provides an opportunity for Eastern European countries to increase their production in agriculture and forestry. At the same time, such economic development must be congruent with the European Union’s long-term climate and biodiversity objectives. As a country that is rich in bioresources, the Latvian case study is highly relevant to many other countries—especially those in Central and Eastern Europe—and faces a choice of transition pathways to meet both economic and environmental objectives. In order to assess the trade-offs between investments in the bioeconomy and the achievement of climate and biodiversity objectives, we used the Functional Land Management framework for the quantification of the supply and demand for the primary productivity, carbon regulation and biodiversity functions. We related the supply of these three soil functions to combinations of land use and soil characteristics. The demand for the same functions were derived from European, national and regional policy objectives. Our results showed different spatial scales at which variation in demand and supply is manifested. High demand for biodiversity was associated with areas dominated by agricultural land at the local scale, while regional differences of unemployment rates and the target for GDP increases framed the demand for primary productivity. National demand for carbon regulation focused on areas dominated by forests on organic soils. We subsequently identified mismatches between the supply and demand for soil functions, and we selected spatial locations for specific land use changes and improvements in management practices to promote sustainable development of the bio-economy. Our results offer guidance to policy makers that will help them to form a national policy that will underpin management practices that are effective and tailored towards local climate conditions and national implementation pathways.